Co-digestion strategies to enhance microalgae anaerobic digestion: A review. (September 2019) - Solé-Bundó, Maria; Passos, Fabiana; Romero-Güiza, Maycoll S.; Ferrer, Ivet; Astals, Sergi
Abstract: Microalgae biorefineries for the production of biofuels and high-value products have captured the attention of academia and industry. Implementing an anaerobic digestion step can enhance resource recovery from microalgae and microalgae residues. Anaerobic co-digestion, the simultaneous digestion of two or more substrates, is an opportunity to overcome the low biodegradability and the risk of ammonia inhibition associated with microalgae and microalgae residues mono-digestion. Besides, microalgae can also be used as co-substrate in biogas plants, with the aim of increasing the organic loading rate while providing alkalinity, macro- and micronutrients. Sewage sludge is the most researched co-substrate for microalgae since microalgae photobioreactors can be used for secondary, tertiary and anaerobic digestion supernatant treatment in wastewater treatment plants. However, microalgae and microalgae residues have been successfully co-digested with a wide variety of wastes, including crops, energy crops, paper waste, animal manure, vinasse, olive mill waste, and fat, oil and grease. Lipid-spent microalgae and glycerol co-digestion has also been largely researched due to the growing interest on microalgal-derived biodiesel. Most studies have assessed the impact of co-digestion on the methane yield and process kinetics through biochemical methane potential (BMP) tests. However, BMP test is not the most suitable method to assess the impact of co-digestion on other important factors such as supernatant nutrient content, digestate dewaterability, biosolids quality, and H2 S concentration in the biogas. Overall, more lab-scale and pilot-scale continuous experiments are needed to get a holistic understanding of microalgal anaerobic co-digestion. Highlights: Co-digestion overcomes the limitations of microalgae anaerobic mono-digestion. Ideal co-substrates boost methane production without increasing the nitrogen load. In WWTPs, sludge can be co-digested with microalgae used for wastewater treatment. Microalgae as co-substrate also provides alkalinity and macro and micronutrients. More research is needed to get a holistic understanding of microalgal co-digestion.